Keselamatan Maritim di Indonesia Akibat Pengaruh dari The International Convention for the Safety of Life at Sea (SOLAS 1974) - Zefanya, Anastasia (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
A report from Research and Markets estimates that the global maritime safety industry will grow from US16.71 billion in 2016 to US23.67 billion in 2021 through factors such as compliance with regulatory standards and guidelines, increased maritime awareness, and an increasing number of incidents of piracy and terrorism.” (Research and Markets: 2016). This paper aims to analyze the role of The International Convention for the Safety of Life at Sea (SOLAS 1974) on maritime safety in Indonesia. And also about Who are the Main Stakeholders of Maritime Safety in Indonesia. This paper aims to increase knowledge about the 1974 Solas convention on developing maritime safety in Indonesia. This paper aims to analyze the role of The International Convention for the Safety of Life at Sea (SOLAS 1974) on maritime safety in Indonesia. And also about Who are the Main Stakeholders of Maritime Safety in Indonesia. This paper aims to increase knowledge about the 1974 Solas convention on developing maritime safety in Indonesia